(untitled)
The estimated glomerular filtration (e-GFR) and serum creatinine is the screening methods of reduced renal function in patients with type-II diabetes (T2DM) in both patient with diabetic nephropathy and with no diabetic nephropathy. The objective of this study was to evaluate the clinical significance of e-GFR in type-II diabetes mellitus patients with diabetic nephropathy and without diabetic nephropathy.This cross-sectional study was conducted from March 2020 to February 2021 in the Department of Laboratory Medicine in collaboration with Department of Nephrology, Bangbandhu Sheikh Mujib Medical University (BSMMU), Dhaka involving 60 patients from the department of Nephrology, BSMMU. Among 60 patients, 30 were with diabetic nephropathy and 30 were without nephropathy. Both nephrop- athy and without nephropathy group were selected according to selection criteria. Random blood sugar (RBS), Glycated hemoglobin (HbA1c), serum creatinine and e-GFR level were measured in all patients. After data collection and processing, all statistical analysis was done by using SPSS Version 26.0. In this study, the mean(